Group differences in health literacy are ameliorated in ehealth literacy. Issue 1 (1st January 2021) - Neter, Efrat; Brainin, Esther; Baron-Epel, Orna
ABSTRACT: Background: Heath literacy and eHealth literacy are skills that enable individuals to seek, understand and use information in ways which promote and maintain health. The present study examined group differences (ethnicity, immigration) in both literacies and whether there exists an association between the literacies and potential outcomes/gains in health behaviors, health care utilization, perceived health and perceived outcomes of Internet search. Methods: Participants included 819 Israeli men and women who responded to a nationally representative random-digital-dial (RDD) telephone survey. Respondents were veteran Jews, immigrants from the Former Soviet Union, and Palestinian Citizens of Israel. Results: Significant differences between the groups were found in health literacy, especially in higher ordered skills, so that the immigrant group was the lowest, after accounting for demographic variables. No significant group differences were found in eHealth literacy. Health literacy was found to be significantly associated with healthcare utilization, perceived health and perceived outcomes of Internet search while eHealth literacy was associated with perceived health and perceived outcomes of Internet search. No interaction was found between group and literacies in the prediction of the outcomes. Conclusions: Immigration hampers health literacy but differences are ameliorated in eHealth literacy. Finding on association between literacies and outcomes replicated previous ones and the absence of moderation by group attests to the robustness of the models on health literacies.